Bispectral EEG Index during Nitrous Oxide Administration - Rampil, Ira J.; Kim, Jin-Soo; Lenhardt, Rainer; Negishi, Chiharu; Sessler, Daniel I. (Anesthesiology (Philadelphia), 1998)
Nitrous oxide (N2O) is a commonly used sedative for painful diagnostic procedures and dental work. The authors sought to characterize the effects of N2O on quantitative electroencephalographic (EEG) variables including the bispectral index (BIS), a quantitative parameter developed to correlate with the level of sedation induced by a variety of agents. Healthy young adult volunteers (n = 13) were given a randomized sequence of N2O/O2 combinations via face mask. Five concentrations of N2O (10, 20, 30, 40, and 50% atm) were administered for 15 min (20 min for the first step). EEG was recorded from bilateral frontal poles continuously. At the end of each exposure, level of sedation was assessed using primarily the Observer Assessment of Alertness/Sedation (OAA/S) scale. One subject withdrew from the study because of emesis at 50% N2O. N2O (50%) increased theta, beta, 40-50 Hz, and 70-110 Hz band powers. BIS and spectral edge frequency during 50% N2O/O2 did not differ significantly from baseline values. Abrupt decreases from higher to lower concentrations frequently evoked a profound, transient slowing of activity. No significant change in OAA/S was detected during the study. Although the spectral content of the EEG changed during N2O administration, reflecting some pharmacologic effect, the subjects remained cooperative and responsive throughout, and therefore N2O can only be considered a weak sedative at the tested concentrations. Despite changes in the lower and higher frequency ranges of EEG activity, the BIS did not change, which is consistent with its design objective as a specific measure of hypnosis.